Overview of the Knowledge Level of Pharmaceutical Technical Personnel on the Prevention of Covid-19 in Balikpapan City - Fitri Handayani (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2024)
Coronavirus disease 19 is a disease caused by a new type of coronavirus, COVID-19. This virus has been declared a pandemic and can spread rapidly through direct human contact. COVID-19 has an impact on pharmaceutical services, especially Pharmaceutical Technical Personel (PTP), therefore it is important to describe the level of knowledge of PTP in preventing COVID-19 in Balikpapan City. The purpose of this study is to describe the level of knowledge of pharmacy technical personnel on COVID-19 prevention in Balikpapan City. This research uses quantitative method, this type of research is descriptive (non-experimental) observational with cross sectional approach. The data of this study were obtained from the research subjects, namely pharmacy technicians working in Balikpapan City through questionnaires. Data analysis method is bivariate analysis and univariate analysis to see the frequency of PTP knowledge level in Balikpapan City on COVID-19 prevention. The results showed that there is a relationship between PTP characteristics on place of work, education, and age with knowledge level on COVID-19 prevention. Meanwhile, PTP characteristics on gender and type of job have no relationship with the level of knowledge on COVID-19 prevention in Balikpapan City. The knowledge level of PTP on COVID-19 prevention in Balikpapan City is obtained by 6.50% in good category, 24.80% in fair category, and 68.70% in poor category.